2002
DOI: 10.1084/jem.20011658
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Selection Generates a Large T Cell Pool Recognizing a Self-Peptide in Humans

Abstract: The low frequency of self-peptide–specific T cells in the human preimmune repertoire has so far precluded their direct evaluation. Here, we report an unexpected high frequency of T cells specific for the self-antigen Melan-A/MART-1 in CD8 single–positive thymocytes from human histocompatibility leukocyte antigen-A2 healthy individuals, which is maintained in the peripheral blood of newborns and adults. Postthymic replicative history of Melan-A/MART-1–specific CD8 T cells was independently assessed by quantifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 50 publications
(91 reference statements)
11
129
1
Order By: Relevance
“…No expansion of ELA‐specific CD8 + T‐cells was observed priming in the absence of peptide (data not shown). Although it is established that ELA‐reactive CD8 + T‐cells in healthy donors can be defined as naïve T‐cells (characterized by a CD45RA + CCR7 + phenotype, a high TREC content and long telomeres) (Dutoit et al ., 2002; Zippelius et al ., 2002), we confirmed that ELA‐specific T‐cell priming in these donors was indeed occurring within the naïve (and not memory) CD8 + T‐cell compartment. For this purpose, we mixed purified naïve or memory CD8 + T‐cells separately with autologous CD8‐depleted PBMCs to initiate priming (Fig.…”
Section: Resultssupporting
confidence: 71%
“…No expansion of ELA‐specific CD8 + T‐cells was observed priming in the absence of peptide (data not shown). Although it is established that ELA‐reactive CD8 + T‐cells in healthy donors can be defined as naïve T‐cells (characterized by a CD45RA + CCR7 + phenotype, a high TREC content and long telomeres) (Dutoit et al ., 2002; Zippelius et al ., 2002), we confirmed that ELA‐specific T‐cell priming in these donors was indeed occurring within the naïve (and not memory) CD8 + T‐cell compartment. For this purpose, we mixed purified naïve or memory CD8 + T‐cells separately with autologous CD8‐depleted PBMCs to initiate priming (Fig.…”
Section: Resultssupporting
confidence: 71%
“…1 and 2. The frequency of MELOE-1-specific T cells is around ten times lower than the frequency of Melan-A-specific T cells (around 1 in 1 Â 10 4 in our study and up to 1 in 1 Â 10 3 in other studies) [13,14,26]. With the exception of the Melan-A antigen, few studies have established ex vivo frequencies of tumor antigenspecific T cells in peripheral blood, their low frequencies precluding their direct evaluation.…”
Section: Discussioncontrasting
confidence: 75%
“…This expression profile and the potential involvement of MELOE-1-specific CTL in modifying time to progression of TIL-treated patients strongly suggest that this antigen is a relevant target for the development of immunotherapy protocols in melanoma; however, a crucial point for the use of a tumor antigen in immunotherapy is the presence and frequency of a tumor reactive T-cell-specific repertoire in melanoma patients [11]. Again, with the exception of Melan-A-specific T cells, which are found at high frequencies (up to 1 in 1 Â 10 3 CD8 1 lymphocytes) in the blood of HLA-A2 1 healthy donors and melanoma patients [12][13][14], the frequencies of other antigenspecific T cells are much lower (in the range of 1 in 1 Â 10 7 for MAGE-A3-specific T cells in healthy donors [15]). Such a high frequency of Melan-A-specific T cells in healthy donors and melanoma patients has been associated with a dominant TCR Va usage by Melan-A-specific T cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that this technique could be applied to the enrichment of such a T cell population, we used Melan-A-specific T cells. Phenotypic [12], functional [13] and molecular techniques [14] have confirmed unequivocally that in normal individuals, these T cells are truly antigen naive. Following enrichment, Melan-Aspecific T cells could be found at a frequency of 83.78% of CD8 + T cells (Fig.…”
Section: Magnetic Selection Of Naive Populations Of Melan-a-specific mentioning
confidence: 86%